2015
DOI: 10.1038/srep17693
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiles delineate mycolactone signature in Buruli ulcer disease

Abstract: Infection of human skin with Mycobacterium ulcerans, the causative agent of Buruli ulcer, is associated with the systemic diffusion of a bacterial macrolide named mycolactone. Patients with progressive disease show alterations in their serum proteome, likely reflecting the inhibition of secreted protein production by mycolactone at the cellular level. Here, we used semi-quantitative metabolomics to characterize metabolic perturbations in serum samples of infected individuals, and human cells exposed to mycolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The peptide discovered from the untargeted analysis in this study— is a cleavage peptide of Fibrinogen A-α. The increase in the concentration of named peptide is not specific to atopic dermatitis but has also been seen in Buruli ulcer [ 32 ], tuberculosis [ 33 ] and diabetes [ 34 ]. The properties of fibrin clot in AD patients’ blood samples have been studied and the analysis revealed an increased clot mass and fiber thickness, faster clot formation among other altered plasma fibrin clot properties [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peptide discovered from the untargeted analysis in this study— is a cleavage peptide of Fibrinogen A-α. The increase in the concentration of named peptide is not specific to atopic dermatitis but has also been seen in Buruli ulcer [ 32 ], tuberculosis [ 33 ] and diabetes [ 34 ]. The properties of fibrin clot in AD patients’ blood samples have been studied and the analysis revealed an increased clot mass and fiber thickness, faster clot formation among other altered plasma fibrin clot properties [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…More extensive multi-analyte profiling of serum proteins in BU patients and endemic controls revealed that, although the disease does not influence significantly the leukocyte composition of the peripheral blood, it impacts an even wider array of circulating molecules [31,66]. Indeed, several of these analytes contribute to acute phase reaction, metabolism, coagulation and tissue remodeling, with some of them already having been implicated in healing speed [31,66]. Specifically regarding metabolic factors, M. ulcerans not only interferes with energy-generation, but also with peptide, lipid and nucleotide pathways [66].…”
Section: Regional and Systemic Responsesmentioning
confidence: 99%
“…Indeed, several of these analytes contribute to acute phase reaction, metabolism, coagulation and tissue remodeling, with some of them already having been implicated in healing speed [31,66]. Specifically regarding metabolic factors, M. ulcerans not only interferes with energy-generation, but also with peptide, lipid and nucleotide pathways [66]. Even though many of these alterations seem to be in line with the expected response of the host to infectious processes, others, as the proposed impairment of the tricarboxylic acid (TCA) cycle, could be the result of a direct effect of mycolactone [66,67].…”
Section: Regional and Systemic Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…117 The core of M. ulcerans-induced lesions becomes consequently bursting with dying cells, with milder effects being observed as it spreads regionally and systemically to more distant organs. [118][119][120][121] The metabolism of M. ulcerans also presents important nuances that influence its pathogenesis. M. ulcerans growth is optimal at 32°C, explaining the lack of systemic dissemination of the infection in BU patients.…”
Section: Introductionmentioning
confidence: 99%